Implementing farmers' rights in genetic resources: Approaches to benefit sharing - Pachico, Douglas H. (2001)
With the advent of biotechnology and the emergence of property rights in genetic materials, the distribution of benefits from genetic resources is an issue of growing importance. Farmer's Rights is a concept that has emerged to seek to insure appropriate compensation to farmers for their contributions to crop improvement and genetic conservation. This paper evaluates crop genetic resources from two points of view: first in terms of royalty incomes that could be earned from seed sales of improved germplasm; and second, in terms of the potential increase in agricultural productivity that could result from improved germplasm. A model to calculate the upper limit of potential royalty incomes is developed and applied to the case of common beans (Phaseolus vulgaris L.). The paper finds that high-income gene-poor countries in the North would indeed make payments under a royalty model system to low-income gene-rich countries in the South, but the magnitude of these payments is quite modest. Much greater payments would flow between gene-poor regions of the South to a few gene-rich countries. The main gainers from the system for beans would be Mexico, Peru and Ecuador, while Brazil and sub-saharan Africa would bear the brunt of the payments. Most countries in the south would have far more to gain from increases in productivity due to utilizing germplasm, than they would from receiving royalty payments for the ownership of germplasm. This model could serve as a basis for calculating benefits sharing formula for the International Fund for Plant Genetic Resources as envisioned by FAO as the mechanism for compensating for Farmers' Rights.